O espaço do jogo: espaço cênico teatro contemporâneo - Cristiano Cezarino Rodrigues (2008)
This study seeks to understand the production of contemporary scenic space by analysing forms of appropriation of urban space by artists and groups that have as a fundamental characteristic of their works not to use conventional spaces or institutionalized ones. Based on the concept of anurban theatre, it is the intention here to verify whether the theatrical event, in the construction of its scenic space, ends up building a new meaning in urban space and also whether this process contributes to its enhacement or not. It also examines whether the urban space is occupied as a neutral space, where a scenario only works as decoration, in other words, as a decorative background for the running of the show, or as an element whose semantic load is taken into account when establishing the location of the event. By means of researching the artisticproduction of the Brazilian group Teatro da Vertigem, this study seeks to understand how it is established the relation between the urban space and the scenic space, and how, drawing from this dialogue, differentiated propositions of architecture and theatre stage design can emerge.